2003
DOI: 10.1196/annals.1299.070
|View full text |Cite
|
Sign up to set email alerts
|

Catha edulis (Khat) Induces Cell Death by Apoptosis in Leukemia Cell Lines

Abstract: Khat is the Celastraceus edulis plant, a flowering evergreen tree or large shrub, which grows in the Horn of Africa and southwestern Arabia. Khat use has been associated with development of oral cancer, but its molecular effects remain controversial. This study describes a novel cytotoxic effect of whole khat extract on three leukemia cell lines. Cells were exposed to khat extract and harvested for analysis by fluorescent and electron microscopy, trypan blue exclusion, as well as immunoblotting to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 6 publications
1
27
0
Order By: Relevance
“…[51], Arnebia nobilis [64], Cimicifuga foetida [65], Brassica oleracea [35], Calendula officinalis [25], Pereskia bleo (Kunth) DC. (Cactaceae) [61], and Catha edulis (Khat) [16].…”
Section: Mediummentioning
confidence: 99%
“…[51], Arnebia nobilis [64], Cimicifuga foetida [65], Brassica oleracea [35], Calendula officinalis [25], Pereskia bleo (Kunth) DC. (Cactaceae) [61], and Catha edulis (Khat) [16].…”
Section: Mediummentioning
confidence: 99%
“…32,33 Potentially malignant white lesions such as Khat-induced leukoplakia have been described in chewers with higher prevalence among those who simultaneously consume tobacco 34 and alcohol. [35][36][37] A large part of the Indian ethnic population in Africa (Kenya, South Africa in particular) still consume areca nut, commonly embedded in betel quid containing shredded tobacco, scented products and slaked lime (Paan masala). It was reported in 1993 that the areca nut is chewed alone by 93% of Indian women in South Africa.…”
Section: Aetiology and Risk Factors Of Oral Cancer In Africamentioning
confidence: 99%
“…In rats, a decreased serum level of free radical metabolising/ scavenging enzymes and glucose has been observed after oral administration, suggesting a deranged systemic capacity to handle oxidative radicals after khat use (Al-Qirim et al, 2002). It has also been reported that khat induces cytotoxic effects in cells (Al-Ahdal et al, 1988;Al-Meshal et al, 1991;Al-Mamary et al, 2002;Dimba et al, 2003) and in lymphoid tissue, and in the liver and kidney after per oral administration to white rabbits (Al-Meshal et al, 1991;Al-Mamary et al, 2002), but the mode of cell death has not so far been addressed.…”
mentioning
confidence: 99%